2006
DOI: 10.1111/j.1464-410x.2006.06169.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced renal function and benefits of treatment in cystinuria vs other forms of nephrolithiasis

Abstract: A significant study from the USA compares cystine stone formers and routine stone formers; the former group had a higher requirement for therapeutic procedures, but this was less if they took chelating agents, although remaining higher than in the latter group. Other interesting findings are also presented. OBJECTIVE First, to compare two types of stone formers (SF), those with cystinuria and those without, for effects of treatments for stones, as cystinuria leads to recurrent stones that are difficult to frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 29 publications
(37 reference statements)
1
42
0
1
Order By: Relevance
“…BP.160/100 mmHg was reported in 25.8% of cystinuric patients (17) and Dahlberg et al reported that 12.4% of cystinuric patients had HBP (36). It has also been reported that HBP was not more common in cystinuric patients than in patients with stones of other causes (17). After excluding risk factors known to be associated with HBP, the available data were too sparse to evaluate the prevalence of HBP in patients aged $40 years.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…BP.160/100 mmHg was reported in 25.8% of cystinuric patients (17) and Dahlberg et al reported that 12.4% of cystinuric patients had HBP (36). It has also been reported that HBP was not more common in cystinuric patients than in patients with stones of other causes (17). After excluding risk factors known to be associated with HBP, the available data were too sparse to evaluate the prevalence of HBP in patients aged $40 years.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that cystinuric patients are overrepresented among nephrolithiasis patients with an acquired solitary kidney (27,28), and that they have significantly more nephrectomy than patients with calcium oxalate nephrolithiasis (15). The prevalence of nephrectomy varies from 7.7% to 20% among cystinuric patients (8,12,15,17,18,29). Stone-former patients with a single functioning kidney have a lower GFR than those with two functioning kidneys (28) and nephrectomy was shown to be a risk factor for elevated PCr in cystinuric patients (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKD is a recognized complication of kidney stones as a result of rare hereditary disorders (e.g., primary hyperoxaluria, Dent disease, 2-8-hydroxyadenine crystalluria, cystinuria) (3)(4)(5), whereby nephrocalcinosis or renal crystal deposition can lead to progressive loss of GFR and ESRD at a young age. In addition, infection stones (struvite) can lead to an obstructive nephropathy with staghorn calculi and are the leading cause of ESRD attributed to nephrolithiasis (6).…”
mentioning
confidence: 99%
“…Urolithiasis is an equally highly prevalent disorder, affecting approximately 10% of the population in Western countries (5)(6) and Japan (7), and renal dysfunction is a well-described complication of urolithiasis (8)(9)(10)(11)(12)(13). Struvite stones, including staghorn calculi and severe stone disease caused by genetic disorders (e.g., primary hyperoxaluria, cystinuria, Dent disease and 2-8-hydroxyadenine crystalluria) (8)(9)(10), are universally considered the most frequent causes of urolithiasis-associated end-stage renal disease (ESRD). On the other hand, it is thought that the more common calcium oxalate or uric acid stones are a painful, but otherwise benign condition, infrequently leading to ESRD.…”
Section: Introductionmentioning
confidence: 99%